Sejarah Ekonomi Negeri Kelantan, 1959-2008 - Awang, Rosmina (2017)
This study analyzes the development of economic history of Kelantan from the year of 1959 till 2008. The objective of this study is focus on the different economy development performance between the PAS and the Barisan Nasional. It also review the policies and program run by trusted agencies. The research method used is based on the research methodology on the sources of resources obtained in libraries and national archives of Malaysia. In addition, face to face interviews are also conducted to obtain relevant information to support the study. The state of Kelantan economic resources are much dependant on the result of agriculture from the past till now. However, the research only focuses on agricultural produce such as paddy, palm oil and rubber in generating the Kelantan economy